Development of Metal Nanoparticle Catalysis toward Drug Discovery - Arisawa, Mitsuhiro (Chemical & pharmaceutical bulletin, 2019)
Transition-metal nanoparticles (NPs) catalysts supported on solid material represent one of the most important subjects in organic synthesis due to their reliable carbon–carbon or carbon–heteroatom bond-forming cross-coupling reactions. Therefore methodologically and conceptually novel immobilization methods for nonprecious transition-metal NPs are currently required for the development of organic, inorganic, green, materials, and medicinal chemistry. We discovered a self-assembled Au-supported Pd NPs catalyst (SAPd(0)) and applied it as a catalyst to Suzuki–Miyaura coupling, Buchwald–Hartwig reaction, Carbon(sp2 and sp3)–Hydrogen bond functionalization, double carbonylation, removal of the allyl protecting groups of allyl esters, and redox switching. SAPd(0) comprises approximately 10 layers of self-assembled Pd(0) NPs, whose size is less than 5 nm on the surface of a sulfur-modified Au. The Pd NPs are wrapped in a sulfated p-xylene polymer matrix. We thought that the self-assembled Au-supported Pd NPs could be made by in situ metal NP and nanospace simultaneous organization (PSSO). This methodology involves 4 kinds of simultaneous procedures: i) reduction of a higher valence metal salt, ii) growth of metal NPs with appropriate size, iii) growth of a matrix with appropriate pores, and iv) wrapping of the metal NPs by matrix nanopores. This methodology is different from previously reported metal NPs-immobilizing methods, which use solid supports with preformed pores or coordination sites. We also applied the in situ PSSO method to prepare various immobilized transition-metal NPs, including base metals. For example, the in situ PSSO method can be applicable to easily prepare Ni, Ru, and Fe NPs with good recyclability and low metal leaching for use in organic synthesis.